Enhancing the Design Process with Drama-Related Methods. (3rd July 2016) - Lawson, Glyn; Brown, Michael; Coughlan, Tim; Floyde, Anne; Baurley, Sharon; Elliott, Meretta; Koppe, Therese; Tsai, Allen
Abstract: This paper presents a critical review of several applications of drama-related methods of design, discussing their benefits and limitations and providing comment on practical aspects of their implementation. Drama-related methods can shed light on the contexts in which a new product will be used, helping to clarify any potential issues users may have with the design. These methods can improve communication and facilitate more fruitful collaboration between the various stakeholders. Improvisation can be used to improve the effectiveness and reliability of brainstorming sessions. However, the level of acting skill required of the participants needs consideration, and must be appropriate to the purpose of the evaluation. Also, drama methods generally add resources to the design process, and there is a lack of validation studies of tangible improvements to the designed product. We provide recommendations for design-drama approaches with the potential to benefit different stages of a product's development.